Reassessing the Muslim Migrant Worker Experience in Japan: An Indonesian Perspective - Dhany Putra Pratama (The Indonesian Islamic Studies and International Relations Association (Insiera), 2025)
This research provides an insight on the reasons behind the difficulty to introduce and promote religious accommodations for Muslim workers in Japan through Indonesian Muslims’ perspectives. As the country progresses into a multicultural society, the Japanese society faces challenges in incorporating and integrating religious communities, particularly Muslims, in Japanese workplaces. Through the scope of multiculturalism and literature research, the difficulty to the provision is caused by a combination of external and internal factors. Additionally, creating a multicultural society leads to the necessity for societal reforms involving not only individuals and non-governmental organizations, but also the potential for local-scale diplomatic relations.